Understanding statistics in the behavioral sciences - Bakeman, Roger (Lawrence Erlbaum Associates, 2005)
Designed to help readers understand research reports, analyze data, and familiarize themselves with the conceptual underpinnings of statistical analyses used in behavioral science literature.